Trichosporon asahii infection of a dialysis PTFE arteriovenous graft - Krzossok, Stefan; Birck, Rainer; Henke, S.; Hof, Herbert; Woude, Fokko J. van der; Braun, Claude (Clinical nephrology, 2004)
Trichosporon species are the causative agents of superficial skin infections, such as white piedra. Immunocompromised hosts, particularly those with underlying hematological malignancy, are at risk of developing invasive infection, which usually progresses to disseminated life-threatening disease. Peritonitis caused by Trichosporon has been described in end-stage renal disease patients treated with continuous ambulatory peritoneal dialysis. Here, we report on a Trichosporon infection of an arteriovenous graft in a patient on chronic hemodialysis. The infection was successfully treated with fluconazole and total surgical resection of the graft.